White Matter Structural Brain Connectivity of Young Healthy Individuals With High Trait Anxiety - Yang, Chunlan; Zhang, Yining; Lu, Min; Ren, Jiechuan; Li, Zhimei (Frontiers in Neurology, 2020)
Background: Although functional brain connectivity in anxiety-related disorders have been studied, brain connectivity in nonclinical populations with high trait anxiety has been rarely reported. Whether structural brain connectivity changes in young healthy individuals with high trait anxiety remains unknown. Methods: Thirty-eight young healthy individuals with high anxiety levels and 34 healthy subjects with low anxiety levels who were matched with age, gender, and education level were recruited. Diffusion tensor images were acquired to analyze white matter connectivity. Two-sample t-test was used for group comparison of weighted networks and graph properties. Results: Different connections were detected in fractional anisotropy and fiber number weighted networks. These connections were widely distributed in various regions, where relative significance was located in inter-hemispheric frontal lobe, frontal-limbic lobe in right intra-hemisphere, and frontal-temporal lobe in ipsilateral hemisphere. However, no significant difference was found in fiber length weighted network and in graph properties among the three networks. Conclusions: The structural connectivity of white matter may be a vulnerability marker. Hence, healthy individuals with high trait anxiety levels are susceptible to anxiety-related psychopathology. The findings may help elucidate the pathological mechanism of anxiety and establish interventions for population susceptible to anxiety disorders.